Diseño y validación de un cuestionario sobre las actitudes de los profesionales sanitarios hacia la recomendación oficial de vacunación antigripal - Fernández-Prada, María; González-Cabrera, Joaquín; Gil De Miguel, Ángel; Huerta-González, Ismael (Revista Española de Salud Pública, 2019)
OBJECTIVE: Actually, there are no studies related to the attitudes of health professionals towards the official recommendation of influenza vaccination, despite the fact that there are numerous investigations that have addressed their own attitude towards vaccination. The objective is to design the Questionnaire on the Attitudes of Healthcare Professionals towards the Official Flu Vaccination Recommendations (CAPSVA). METHODS: Quasi-experimental study. The control group includedInstrumental study was conducted between February and March 2019 with 288 professionals of Medicine, Nursing and Pharmacy of the Principado of Asturias (Spain). The sampling was non-probabilistic of incidental type. After content validation, a tool was designed with 16 items in three dimensions. Reliability (alpha ordinal) and internal validity (exploratory factorial analysis using the parallel analysis method) analyses were performed, as well as frequency analysis and mean comparisons. RESULTS: The exploratory factor analysis yielded a 3-factor solution that explained 79.38% of the total variance. The ordinal alpha ranged from 0,72 to 0,80. The test-retest recorded a value of r= 0,804 (p < 0,001). There were no statistically significant differences when comparing according to sex (p = 0,952), professional group (p = 0,563) or having received influenza vaccination in the last campaign (p = 0,861). There were these differences when comparing the number of years of professional practice (p = 0,003) and having received specific training in vaccines in the last year (p = 0,004). More than 90% of the participants valued positively the influenza vaccination strategy of the Autonomous Community of study (quadrivalent vaccine for < 65 years and adjuvant trivalent for ≥65 years). CONCLUSIONS: A questionnaire with sufficient guarantees of reliability and internal validity is available to evaluate the attitudes of health professionals towards the official recommendation of influenza vaccination.
Design and validation of a questionnaire on the attitudes of health professionals towards the official recommendation of influenza vaccination
OBJETIVO: A día de hoy no existen estudios relacionados con las actitudes de los profesionales sanitarios hacia la recomendación oficial de vacunación antigripal, a pesar de que son numerosas las investigaciones en las que se ha abordado la propia actitud de los mismos hacia su vacunación. El objetivo de este trabajo fue diseñar el Cuestionario sobre las Actitudes de los Profesionales Sanitarios hacia la Recomendaciones Oficiales de Vacunación Antigripal (CAPSVA). METODOS: Estudio instrumental realizado entre febrero y marzo de 2019 con 288 profesionales de Medicina, Enfermería y Farmacia del Principado de Asturias (España). El muestreo fue no probabilístico de tipo incidental. Tras la validación de contenido, se diseñó una herramienta con 16 ítems en tres dimensiones. Se realizaron análisis de fiabilidad (alfa ordinal) y validez interna (análisis factorial exploratorio mediante el método de análisis paralelo), además de análisis de frecuencias y comparaciones de medias. RESULTADOS: El análisis factorial exploratorio arrojó una solución de 3 factores que explicó el 79,38% de la varianza total. El alfa ordinal osciló entre 0,72 y 0,80. El test-retest registró un valor de r= 0,804 (p < 0,001). No hubo diferencias estadísticamente significativas al comparar según la variable sexo (p = 0,952), grupo profesional (p = 0,563) o haber recibido la vacunación antigripal en la última campaña (p = 0,861). Sí las hubo al comparar el número de años de ejercicio profesional (p = 0,003) y haber recibido formación específica en vacunas en el último año (p = 0,004). Más de un 90% de los participantes valoró positivamente la estrategia de vacunación antigripal de la Comunidad Autónoma de estudio (vacuna cuadrivalente para < 65 años y trivalente adyuvada para ≥65 años). CONCLUSIONES: Se dispone de un cuestionario con suficientes garantías de fiabilidad y validez interna para evaluar las actitudes de los profesionales sanitarios hacia la recomendación oficial de la vacunación antigripal.
Keywords: attitudes; health professionals; influenza; medicine; nursing; questionnaire; Spain; vaccination; Scopus; JCR